Mobilizing the community to help students succeed - Price, Hugh B. (Alexandria, VA : Association for Supervision and Curriculum Development, 2008)
Offers advice to educators on how to motivate students to succeed in school and in life through community-based programs.
Understanding the challenge -- Boosting student motivation -- Celebrating student achievement -- Promoting academic success -- Mobilizing the village.
Includes bibliographical references (p. 129-133) and index.
Professional
Keywords: Academic achievement -- United States; Community and school -- United States; Education -- Social aspects -- United States; Motivation in education -- United States -- Citizen participation; Academic achievement -- United States; Community and school -- United States; Education -- Citizen participation; Education -- United States -- Social aspects; Motivation (Psychology)